Optimizing the Role of Cadres and Families through Education and Digital Technical Guidance DOTS Management in Improving Tuberculosis Treatment Adherence - Nela, Ari Sukma; Azka, Laisa; Patria, Armen (Jurnal Kreativitas Pengabdian Kepada Masyarakat (PKM), 2025)
ABSTRACT Tuberculosis (TB) remains one of the main challenges in the field of health in Indonesia, marked by high incidence rates and high rates of treatment discontinuation. Patient compliance in following treatment is key to the success of therapy. In previous community service activities, the role of health cadres and family support in the implementation of DOTS (Directly Observed Treatment Short-course) management has been carried out, but still needs to be optimized. This is because the manual data collection system is considered quite cumbersome and has an impact on the low achievement of TB control program indicators, which are far from the expected targets. Therefore, one of the new strategies designed is the implementation of digital-based technical guidance (bimtek). This activity aims to improve the role of cadres and families through education and digital technical guidance on DOTS management in order to improve TB patient compliance. The activity was carried out over a period of one month, consisting of socialization, group education, and participatory training, including counseling, mentoring, and the use of interactive digital media. There were 30 participants, consisting of health cadres, patients' families, and community leaders in the Gedong Tataan Community Health Center area. Preparations took two weeks, while the implementation took place over two days offline. Evaluation was conducted using pre-tests, post-tests, observations, and satisfaction questionnaires. The results of the activity showed an increase in the knowledge and skills of cadres and families, the use of digital applications, and patient compliance with therapy up to 78%. Digital education and technical guidance on DOTS management proved to empower the community in supporting TB control. In conclusion, DOTS-based digital education and technical guidance can empower cadres and families in supporting TB patient treatment, thereby increasing the success of TB control programs in the community. Keywords: Tuberculosis, DOTS, Treatment Adherence, Health Cadres, Digital Education